Percepción del riesgo de adquirir una Infección de Transmisión Sexual en adolescentes Risk perception to contract sexually transmitted infections from adolescents - Meneses Acosta, María Elena (2017)
A descriptive transversal study to determine the adolescents’ risk perception to contract sexually transmitted infections (STIs) was performed after collecting data from 555 students from the Junior High School “Rafael Valdez Pérez”. The school is located in the municipality of San Antonio de los Baños, Artemisa, Cuba. A survey was applied to students in 7th, 8th and 9th grades, the data was processed by percentage calculation and was tabulated. A high proportion of the respondents were male teenagers encompassing the three grades. The respondents’ parents were shown to have predominantly high school, colleges and university education. A regularity was found for students who do not live with both parents. The main source about STIs information among the students was the television. It was concluded that adolescents with low levels of knowledge about STIs had a lower Percepción del riesgo de adquirir una Infección de Transmisión Sexual en adolescentes Risk perception to contract sexually transmitted infections from adolescents Autores: María Elena Meneses Acosta Universidad Nacional de Chimborazo Digna Edelsys Hernández Meléndrez Universidad Nacional de Chimborazo Carlos Gafas González. Universidad Nacional de Chimborazo. Ecuador. cgafasg@gmail.com. 0995174876. REE 8(1) Artículos de temas libres 2 REE Volumen 8 (1) Riobamba ene. - jun. 2014. risk perception of the infections than those with high risk perception of contracting this illnesses.